The PKZ1 Recombination Mutation Assay: A Sensitive Assay for Low Dose Studies - P. J. Sykes; A. A. Morley; A. M. Hooker (SAGE Publishing, 2006)
The majority of mutation studies are performed at high doses of DNA damaging agents due to the insensitivity of most mutation assays. Extrapolation using a linear no-threshold (LNT) dose response model is then used to estimate the extent of possible DNA damage at lower doses. There is increasing evidence to suggest that the LNT model may not be correct at low doses of at least some DNA damaging agents. The pKZ1 in vivo and in vitro recombination assays have proven to be very sensitive for detection of changes in chromosomal inversion in lymphoid tissue in response to low doses of DNA damaging agents. Non-linear dose response curves for chromosomal inversion as an end-point have been identified at low doses of DNA damaging agents using this assay. Here, we review the inversion results obtained to date with the pKZ1 assays and discuss their suitability for low dose studies.